Evaluación de la degradación del suelo en sistemas de producción porcina extensiva al aire libre en la finca “Las Hermanas Domínguez” - Mendoza Canchingre, Brigith Mikaela (2026)
Extensive outdoor pig farming generates environmental pressures on the soil, mainly due to compaction, nutrient loss, and microbial proliferation. The objective of the study was to determine the level of soil degradation on ‘Las Hermanas Domínguez’ farm under extensive pig production. The methodology combined inductive-deductive and analytical-synthetic methods, supported by observation techniques, checklists, simple random sampling, and laboratory analysis of physicochemical (pH, EC, nutrients, texture) and microbiological (E. coli, total mesophiles) parameters. In addition, the Batelle-Columbus matrix was applied to quantify the environmental impact on the edaphic environment. The results showed significant alterations in the contact areas: slightly alkaline pH (7.4–7.8), increasement of electrical conductivity (6.53 dS/m), reduction in clay (24% to 6%), and calcium (24 to 18 meq/100 ml). At the biological level, mesophile counts of 3.58 × 10⁶ CFU/g and the presence of E. coli at 1.59 × 10⁴ NMP/100 g were recorded. The Batelle-Columbus matrix yielded an Environmental Quality Index of 40.54%, classifying the soil as degraded. It is concluded that extensive pig production accelerates soil degradation and that the proposed good practice guide is an essential tool for mitigating impacts.